Does an environmental Kuznets curve exist for changing land use? Empirical evidence from major states of India. (12th May 2004) - Kumar, Pushpam; Aggarwal, Suresh Chand
Varied environmental quality in terms of NOx, SOx etc. has been demonstrated as being associated with the per capita income of a specific region or/country, known as the environmental Kuznets curve (EKC) in the form of an inverted U-shaped curve. Recently, many attempts have been made to examine this relationship in different contexts. This paper analyses the change in land-use pattern for 19 major states of India for 1963–64 to 1995–96. By specifying a suitable model, cropped area, removal of forest cover (deforestation) and pasture area have separately been regressed on per capita income, yield and population density. Besides OLS, the models for the analysis included the Kmenta model, the fixed effect model and the random effect model. Stationarity and cointegration have also been tested for the variables. Results from the analysis indicate the presence of an EKC for crop area at an income level between Rs.1347 and Rs.1440 and for pasture area between the income levels of Rs.881 and Rs.871. The turning point is found to be around Rs.811 for total forest area. The state level analysis confirms the existence of a turning point for crop area for the states of Punjab and Haryana and for total forest area for the states of Punjab and Maharastra.